Anti-biofouling adsorptive sheet based on polyethersulfone/ dried algal biomass / ZnO nanoparticles for dyes removal - Doaa Hussein; Ahmed E. Abdelhamid; Mohamed Gad; Einas El-shatoury; Ahmed Labena (Scientific Reports)
Abstract This study aims to develop an environmentally friendly composite matrix for removing dyes from wastewater. The composite matrix was prepared by incorporating finely ground biomass of the seaweed Sargassum dentifolium (S) and zinc oxide nanoparticles (ZnO) into polyethersulfone (PES) forming composite sheets (PES-S-ZnO). Composite sheets were characterized by Attenuated Total Reflectance Fourier Transform Infrared (ATR)-FTIR, Scanning Electron Microscopy (SEM), and Energy dispersive X-ray (EDX), as well as the swelling behavior, porosity & leaching of ZnO nanoparticles from the sheets were determined. The composite sheet with 20% Sargassum, has proven to be the most effective dye bio-sorbent. Crystal violet (CV), Methylene blue (MB) and Congo red (CR) were successfully removed from the contaminated waters within 6, 6 and 12 h, with removal efficiency of 92.46, 93.10 and 37.96%, respectively. Langmuir isotherm and pseudo-second order kinetic studies could explain the composite bio-sorbent behavior. Furthermore, the recovery and reuse results confirmed that the polymer sheets have stable performance after 5 cycles. The accelerated weathering for the composite sheets indicated that the incorporation of Sargassum biomass into the sheets increased the probability of sheets’ degradation. Furthermore, increasing the ZnO nanoparticles in sheets leads to an increase in anti-biofouling and the degradation performance of the sheets.